Religion and Health in Arctic Norway–the association of religious and spiritual factors with suicidal behaviour in a mixed Sámi and Norwegian adult population - The SAMINOR 2 Questionnaire Survey - Kiærbech, Henrik; Silviken, Anne; Lorem, Geir F; Kristiansen, Roald E; Spein, Anna Rita (International Journal of Circumpolar Health, 2021)
Given the higher suicide rates among the adult population in the northernmost part of Norway and some unfavourable psychosocial outcomes associated with the Laestadian revival movement in this region, it is reasonable to investigate the relationship between religiosity/spirituality and suicidal behaviour in this context. This study used cross-sectional data from the population-based SAMINOR 2 questionnaire survey (2012; n = 11,222; 66% non-Sámi; 22% Laestadian-affiliated; 27% response rate) in mixed Sámi-Norwegian areas of Mid and North Norway. We analysed the associations between religious/spiritual factors and lifetime suicidal ideation and attempts, age at the first attempt, motives, and number of attempts. Multivariable-adjusted regression models considering sociodemographics, Sámi background and self-ascription, and health-related risk factors were applied. Sámi and Laestadian affiliations were significantly associated with religious self-ascription, regular attendance, and Established Church membership. In a fully adjusted model, Laestadian family background was negatively associated with lifetime suicide attempts (OR = 0.66, 95% CI: 0.47–0.93) compared with other family circumstances, whereas regular religious participation was inversely associated with suicide ideation (OR = 0.74, 95% CI: 0.61–0.91) compared with non- or rare attendance. The findings suggest that Laestadianism and religious attendance contribute to less suicidal behaviour among adults in Sámi-Norwegian areas.